Voltage-Sensitive K+ Channels Inhibit Parasympathetic Ganglion Transmission and Vagal Control of Heart Rate in Hypertensive Rats - Berg, Torill (Frontiers in Neurology, 2015)
Parasympathetic withdrawal plays an important role in the autonomic dysfunctions in hypertension. Since hyperpolarizing, voltage-sensitive K+ channels (KV) hamper transmitter release, elevated KV-activity may explain the disturbed vagal control of heart rate (HR) in hypertension. Here, the KV inhibitor 3,4-diaminopyridine was used to demonstrate the impact of KV on autonomic HR control. Cardiac output and HR were recorded by a flow probe on the ascending aorta in anesthetized, normotensive (WKY), and spontaneously hypertensive rats (SHR), and blood pressure by a femoral artery catheter. 3,4-diaminopyridine induced an initial bradycardia, which was greater in SHR than in WKY, followed by sustained tachycardia in both strains. The initial bradycardia was eliminated by acetylcholine synthesis inhibitor (hemicholinium-3) and nicotinic receptor antagonist/ganglion blocker (hexamethonium), and reversed to tachycardia by muscarinic receptor (mAchR) antagonist (atropine). The latter was abolished by sympatho-inhibition (reserpine). Reserpine also eliminated the late, 3,4-diaminopyridine-induced tachycardia in WKY, but induced a sustained atropine-sensitive bradycardia in SHR. Inhibition of the parasympathetic component with hemicholinium-3, hexamethonium, or atropine enhanced the late tachycardia in SHR, whereas hexamethonium reduced the tachycardia in WKY. In conclusion, 3,4-diaminopyridine-induced acetylcholine release, and thus enhanced parasympathetic ganglion transmission, with subsequent mAchR activation and bradycardia. 3,4-diaminopyridine also activated tachycardia, initially by enhancing sympathetic ganglion transmission, subsequently by activation of norepinephrine release from sympathetic nerve terminals. The 3,4-diaminopyridine-induced parasympathetic activation was stronger and more sustained in SHR, demonstrating an enhanced inhibitory control of KV on parasympathetic ganglion transmission. This enhanced KV activity may explain the dysfunctional vagal HR control in SHR.